PHARMACOKINETIC AND PHARMACODYNAMIC INTERACTION BETWEEN LUMIRACOXIB AND FLUVASTATIN: Pharmaceutical Science-Pharmacology - ANBU, JAYARAMAN; ANJANA, ASHWINI; C. ROOSEWELT; RAO, G. SRINIVASA; R. SATHISH (International Journal of Life Science and Pharma Research, 2012)
The present study was carried out to investigate the pharmacokinetics and pharmacodynamic interaction between Lumiracoxib (20mg/kg p.o.) and Fluvastatin (5mg/kg p.o.) alone and their combination in rats by open labeled parallel study design. The animals were maintained on a standard laboratory conditions and were divided into 3 and 6 groups for Pharmacokinetic and Pharmacodynamic studies respectively